Pengaruh Kecerdasan Emosional, Gaya Belajar Visual, Gaya Belajar Auditorial dan Gaya Belajar Kinestetik Pada Tingkat Pemahaman Akuntansi - Pramesti, Ni Made Inten; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p10, 2020)
The level of one's accounting understanding can be influenced by emotional intelligence, visual learning styles, auditory learning styles and kinesthetic learning styles that exist within students. The purpose of the study was to determine the effect of emotional intelligence, visual learning style, auditory learning style and kinesthetic learning styles on the level of understanding of accounting. The research was conducted at the Faculty of Economics and Business, Udayana University. Respondents were 171 students majoring in accounting undergraduate program 2015 were determined by probability sampling method. Data were analyzed by multiple linear regression. Based on the results of the analysis, emotional intelligence has a positive effect on the level of accounting understanding. This shows that the better the emotional intelligence possessed by students causes the level of understanding of accounting increases. Visual learning style, auditory learning style and kinesthetic learning style have a positive effect on the level of understanding of accounting, this shows the better the learning style, the higher the level of understanding of accounting. The implications of the results of this study support cognitive theory which states the level of understanding of accounting is influenced by internal factors, namely emotional intelligence, visual learning style, auditory learning style and kinesthetic learning style. Keywords: Understanding, Intelligence, Learning Style